Modélisation des déterminants et des retombées de l’application des connaissances issues de la recherche psychosociale : Partie II étude de validation - Chagnon, F; M.-J Gervais (2011)
Keywords: Chercheur; Determinant; Mesure; Modèle; Multidisciplinaire; Partenariat; Rapport

La mobilisation des connaissances en protection de l’enfance - Nico Trocmé; Tonino Esposito; Claude Laurendeau; Wendy Thomson; Lise Milne (Criminologie, 2009)
Keywords: article théorique; Determinant; Gestionnaires; Impact; Jeunes et familles en difficulté; Mesure; Organisation; Savoirs; Stratégie; Théorie

The Extent and Organizational Determinants of Research Utilization in Canadian Health Services Organizations - Belkhodja, Omar; Amara, Nabil; Landry, Réjean; Ouimet, Mathieu (Science Communication, 2007)
This article focuses on the use of research by managers and professionals in Canadian health service organizations (ministries, regional authorities, and hospitals). The results of the analysis of the 928 responses underlined the important role that the absorption, learning, culture, and linkage mechanism variables played in determining utilization. General linear regression and regression by organizational type confirmed the importance of the linkage mechanisms, research experience, unit size, and research relevance for the users. The emphasis could thus be put, according to the organization type, on research experience, linkage mechanisms, unit size, research culture, research relevance for the users, and research activities. The article also underscores the individual and organizational contextual factors’ high degree of significance by expressing these contextual factors as organizational variables and by adopting a more organizational perspective of knowledge utilization analysis.
Keywords: Determinant; Étude quantitative; Mesure; Organisation; Social; Théorie

Research use in the Australian child and family welfare sector - Holzer, P; Lewig, K; Bromfield, L; Arney, F (2007)
Keywords: Determinant; Étude quantitative; Gestionnaires; Jeunes et familles en difficulté; Mesure; Praticiens; Stratégie